Application of the Healing BodySoul Architecture Theme in the Space Design of the Rehabilitation Center for Sexual Harassment Victims in Sooko, Mojokerto Regency, East Java - Hafid, Ridho Hati; Ramadhani, Suci; Poedjioetami, Esty (Faculty of Civil Engeneering and Planning - ITATS, 2024)
. The highest number of cases of sexual harassment in the major cities are beginning to circulate in one of the eastern Java provinces, precisely in the district of Mojokerto.To a good objective from macro behavioral concepts to micro-centric concepts, and functional becomes an emphasis in the planning and management of land, shape and space in the Sexual Harassment Rehabilitation Center in Mojokerto Cab.The importance of the literacy it has and one of the contributing factors is the amount of data on sexual harassment.Inspired by the case marks in the surrounding neighborhood of Mojokerto, the idea was created to create a rehabilitation center located in Mojokorto. Lifting the healing theme of the architectural bodysoul can be done by creating an atmosphere that boosts the mood and refreshes the mind by creating spaces that can create a positive state of mind. Therefore this design has different colors, textures, and shapes to produce a friendly and pleasant atmosphere. The natural material used can help boost positive energy and help improve the physical and mental health of its inhabitants.